2006
DOI: 10.1038/sj.jid.5700146
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Eight Tissue Kallikreins in the Stratum Corneum and Sweat

Abstract: Human tissue kallikreins are a family of 15 trypsin or chymotrypsin-like secreted serine proteases (kallikrein protein (hK1-hK15) found in a variety of tissues (Yousef and Diamandis, 2001). In the stratum corneum (SC), we previously quantified hK5, hK6, hK7, hK8, hK10, hK11, hK13, and hK14 as candidates of desquamation-related proteases and compared the hK levels among various age groups (Komatsu et al., 2005a). For sweat, hK1, hK2, and hK7 levels were quantified previously (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 17 publications
(16 reference statements)
6
54
0
Order By: Relevance
“…Our findings were in good agreement with the previously reported KLK levels measured by ELISA. For example, concentration of endogenous KLK6 in sweat previously measured with ELISA was found in the range 1-50 g/g of total protein (48). To the best of our knowledge, the present study reports for the first time the mass spectrometric detection of KLKs 1, 6, 9, 10, and 13 in human sweat.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our findings were in good agreement with the previously reported KLK levels measured by ELISA. For example, concentration of endogenous KLK6 in sweat previously measured with ELISA was found in the range 1-50 g/g of total protein (48). To the best of our knowledge, the present study reports for the first time the mass spectrometric detection of KLKs 1, 6, 9, 10, and 13 in human sweat.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, normalization of results for total protein is crucial. Kallikreins 5,6,7,8,10,11,13, and 14 have been previously quantified in sweat by ELISA (48) and KLKs 5,7,8, and 11 have been previously detected by shotgun proteomics (49 -51). Using the proposed SRM assay, we were able to detect and quantify nine KLKs in sweat (KLKs 1, 5, 6, 7, 8, 9, 10, 11, and 13).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, KLK5 activation of pro-KLK8 may be important physiologically as normal human epidermal cell turnover occurs in the span of 2-4 weeks. Furthermore, expression data suggest that immunoreactive KLK8 concentration in normal human SC tissue extracts is about 4-fold higher than KLK5 (21). Hence, this activation process may occur quicker had we used a pro-KLK8:KLK5 molar ratio of 1:4 or 1:1 instead of 1:10.…”
Section: Mat-klk8 Autodegradation Leads To In Vitro Enzymaticmentioning
confidence: 99%
“…We recently showed that additional trypsin-like KLK peptidases, including KLK6, KLK8, KLK10, KLK11, and KLK13, co-exist with KLK5, KLK7, and KLK14 in stratum corneum tissues, hair follicles, and sebaceous and sweat glands (20,21). Interestingly, we found KLK8 to be the most abundant trypsin-like KLK in normal stratum corneum and sweat, among the seven KLKs tested (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation